Semantics Analysis of Hyponym in The “Fate and Furious 8” - Lailatuz Zakiyah; Zakrimal Zakrimal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to find the hyponym hierarchy and find out the relationship in Fate and Furious 8. The method in this research is descriptive qualitative using observations and non-participatory in collecting data and using informal methods in presenting results. Data were analyzed based on the association with hyponym by referring to semantic analysis. There are found 50 words included in hyponym. There are several categories of hyponym found such as family, transportation, color, appearance, number, object, country, size, animals, and parts of body. Then broken down into (8) hyponym of the family, (7) hyponym of transportation, (3) color of hyponym, (1) hyponym of appearance, (11) hyponym of numbers, (6) hyponym of objects, (4) hyponym of country, (2) hyponym of size, (3) hyponym of animal and (5) hyponym with parts of body. Based on the result, the conclusion can be taken that hyponym of number is the most dominant of hyponym categories. Keywords: Semantic, Lexical Relation, Hyponym